Pengaruh Perkembangan Ragam Bahasa terhadap Perkembangan Kognitif Anak di Era 4.0 - Budiman, Budiman; Panggabean, Alimatusakdia; Rahma, Alya (El-Mujtama: Jurnal Pengabdian Masyarakat, 2024)
Responses to the Ragam Bahasa idea over time have included both advantages and disadvantages. Ragam Bahasa programs' rapid expansion in early education facilities raises questions about their potential effects on the children's cognitive and linguistic development. The opposing party claimed that the youngster would talk slowly, however several research produced different findings. This study will look at how children who participate in a Ragam Bahasa program at school are developing cognitively. Keywords: Ragam Bahasa, early childhood, cognitive, development